Perlindungan Hukum Bagi Konsumen Atas Praktik Pembulatan Nilai Berat Timbangan Oleh Perusahaan Jasa Ekspedisi - Ayu Dwi Ningrum; Johannes Ibrahim Kosasih; I Made Aditya Mantara Putra (Fakultas Hukum Universitas Warmadewa, 2024)
Freight forwarders have the authority to set tariffs according to company policy, because there are no regulations governing tariffs followed by all freight forwarders, especially in legislation. The existence of the legal vacuum in question causes inconsistencies in the Consumer Protection Law with the Regulation of the Minister of Transportation, and raises problems related to the practice of rounding the value of weighing scales. The formulation of this research problem: 1). How is the legal regulation of the practice of rounding the weight value of the scales by the expedition service company; 2). How is legal protection for consumers for losses due to the practice of rounding the weight value of the scales carried out by the expedition service company. The research method used is normative research with a statutory approach and conceptual approach. The results of this study, the practice of rounding the scales is not in accordance with the provisions in the GCPL Law, the implementation of this practice is based on the company's internal decision without official rules being regulated. If consumers suffer losses by business actors, consumers are protected by the GCPL, whose forms of protection are divided into preventive protection and repressive protection.